2022
DOI: 10.21203/rs.3.rs-1936750/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of cryotherapy combined with intralesional tuberculin purified protein derivative (PPD) versus intralesional tuberculin PPD monotherapy in the treatment of multiple common warts

Abstract: Introduction: Intralesional antigen immunotherapy represents a promising therapeutic approach for the treatment of different types of warts, particularly if multiple and/or recalcitrant.Aim: This work aimed to investigate the efficacy and safety of combined cryotherapy with intralesional purified protein derivative (PPD) immunotherapy in the treatment of multiple common warts.Methods: Fifty patients were randomly divided into two groups (25 patients each): Group A: receiving intralesional PPD immunotherapy, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…6 sessions Target warts: A: 77.1 B: 0 C: 18.2 Distant warts: A: 85.7 A: 8.6 B: 5.9 C: 24.2 6 C: pain, blister, erythema, swelling, hyperpigmented scar None observed on PPD and placebo group Awad et el. 23 2022 (Egypt) RCT PPD (A) Cryo-therapy + PPD (B) A: 25 B: 25 Simple, recalcitrant; common Group A: Test dose: 0.1 mL PPD-5TU, intradermal on forearm Treatment: volume injected determined by the size of skin test reactivity according to Kus et al 13 (intralesion on largest wart) Group B: cryotherapy applied for all lesions using liquid nitrogen spray at a distance of 1 cm, margin 1–2 mm (single freezing cycle) followed by intralesional PPD injection into the largest wart 2-weeks interval, max. 4 sessions A: 48 B: 44 A: 20 B: 0 2 Both groups: pain, redness, edema B: blistering, hypopigmentation Awad et al 24 2022 (Egypt) RCT PPD (1) Zinc sulfate 2% (2) 1: 60 2: 60 (pediatric) Simple, recalcitrant; common, plantar, anogenital Group 1: 0.1 mL PPD, intralesion on largest wart Group 2: Zinc sulfate 2%, intralesion on largest wart 2-weeks interval, max.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 sessions Target warts: A: 77.1 B: 0 C: 18.2 Distant warts: A: 85.7 A: 8.6 B: 5.9 C: 24.2 6 C: pain, blister, erythema, swelling, hyperpigmented scar None observed on PPD and placebo group Awad et el. 23 2022 (Egypt) RCT PPD (A) Cryo-therapy + PPD (B) A: 25 B: 25 Simple, recalcitrant; common Group A: Test dose: 0.1 mL PPD-5TU, intradermal on forearm Treatment: volume injected determined by the size of skin test reactivity according to Kus et al 13 (intralesion on largest wart) Group B: cryotherapy applied for all lesions using liquid nitrogen spray at a distance of 1 cm, margin 1–2 mm (single freezing cycle) followed by intralesional PPD injection into the largest wart 2-weeks interval, max. 4 sessions A: 48 B: 44 A: 20 B: 0 2 Both groups: pain, redness, edema B: blistering, hypopigmentation Awad et al 24 2022 (Egypt) RCT PPD (1) Zinc sulfate 2% (2) 1: 60 2: 60 (pediatric) Simple, recalcitrant; common, plantar, anogenital Group 1: 0.1 mL PPD, intralesion on largest wart Group 2: Zinc sulfate 2%, intralesion on largest wart 2-weeks interval, max.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies found no statistically significant relationship between baseline characteristics of the study participants, such as age, duration, number, and type of warts, with the therapeutic response to PPD. However, Awad et al 23 and Jaiswal et al 38 reported younger age of patients among the good responders compared to the minimal or non-responders. The weaker immunological response with increasing age might cause this.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation